In situ application of porous particles in delaying asphalt ravelling - Abedraba Abdalla, Mariam (2024)
Asphalt is one of the most widely used materials for road surfacing due to its cost-effectiveness, durability, and flexibility. However, as it is susceptible to temperature changes and traffic loading, it can deteriorate and require regular maintenance. Common surface distress types like cracking and ravelling, if not treated, can lead to significant pavement damage. To address these issues, recent advances in pavement engineering have introduced innovative materials in asphalt design aimed at improving asphalt performance and promoting more sustainable road infrastructure.